2019
DOI: 10.1177/1545968319826052
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Primary Motor Cortex Inhibition on Upper Limb Impairment and Function in Chronic Stroke: A Multimodal Study

Abstract: Background. Stroke is a leading cause of adult disability owing largely to motor impairment and loss of function. After stroke, there may be abnormalities in γ-aminobutyric acid (GABA)-mediated inhibitory function within primary motor cortex (M1), which may have implications for residual motor impairment and the potential for functional improvements at the chronic stage. Objective. To quantify GABA neurotransmission and concentration within ipsilesional and contralesional M1 and determine if they relate to upp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 53 publications
(85 reference statements)
1
14
0
Order By: Relevance
“…Mooney et al compared chronic stroke patients and HC based on LICI and investigated its correlation with GABA concentration measured with magnetic resonance spectroscopy. LICI was found to be enhanced in chronic stroke patients relative to HC in the ipsilesional motor cortex (p < 0.001), whereas there was no significant association between LICI and metabolite concentrations in stroke patients and HC (142).…”
Section: Lici In Patients With Strokementioning
confidence: 82%
See 1 more Smart Citation
“…Mooney et al compared chronic stroke patients and HC based on LICI and investigated its correlation with GABA concentration measured with magnetic resonance spectroscopy. LICI was found to be enhanced in chronic stroke patients relative to HC in the ipsilesional motor cortex (p < 0.001), whereas there was no significant association between LICI and metabolite concentrations in stroke patients and HC (142).…”
Section: Lici In Patients With Strokementioning
confidence: 82%
“…Studies have presented mixed results in stroke. Studies that found alterations in LICI discussed the methodological differences (using single ISI vs. using range of ISI) as an explanation for the discrepancy between studies (142). On the other hand, it has been consistently shown that LICI has not changed after interventions.…”
Section: Lici In Patients With Strokementioning
confidence: 99%
“…Multimodal studies are vital to interpret the potentially conflicting results between modalities. A recent study using both TMS and MRS described no significant differences in TMS-derived measurements of GABA A activity between patients and controls 57 . However, the authors reported a significant reduction in [GABA] in both hemispheres in the same patients.…”
Section: Excitation–inhibition Balance In Stroke Pathophysiologymentioning
confidence: 92%
“…TMS studies have shown that, as in the early stages of stroke recovery, overall cortical excitability is decreased in the ipsilesional hemisphere compared to both the contralesional hemisphere and healthy age-matched controls 50 . A number of human MRS studies have demonstrated a decrease in [GABA] in the ipsilesional hemisphere at rest in chronic stroke patients 55 – 57 . However, GABA A -mediated inhibition measured using SICI does not differ significantly between the ipsilesional hemisphere and either the contralesional hemisphere or healthy age-matched controls 50 .…”
Section: Excitation–inhibition Balance In Stroke Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation